First measurement of the ratio B(t → Wb)/B(t → Wq) and associated limit on the Cabibbo-Kobayashi-Maskawa element ΙVtbΙ - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2001)
The ratio of the branching fraction from particle collisions were measured. The data was recorded by the Collider Detector at fermilab during the Tevatron run. The measured values were in agreement with the standard model predictions. The measurements yielded a limit on the Cabibbo-Kobayashi-Maskawa quark mixing matrix element.